2014
DOI: 10.1073/pnas.1406768111
|View full text |Cite
|
Sign up to set email alerts
|

Hampered long-term depression and thin spine loss in the nucleus accumbens of ethanol-dependent rats

Abstract: Alcoholism involves long-term cognitive deficits, including memory impairment, resulting in substantial cost to society. Neuronal refinement and stabilization are hypothesized to confer resilience to poor decision making and addictive-like behaviors, such as excessive ethanol drinking and dependence. Accordingly, structural abnormalities are likely to contribute to synaptic dysfunctions that occur from suddenly ceasing the use of alcohol after chronic ingestion. Here we show that ethanol-dependent rats display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 66 publications
7
69
3
Order By: Relevance
“…Together with a meta-analysis of rodent studies, our data provide convergent evidence that a hyperdopaminergic state occurs during protracted abstinence. According to the literature and the time-course studies we present here, we propose that dynamical changes take place in the mesolimbic DA system during withdrawal and protracted abstinence, resulting in a hypodopaminergic state that characterizes acute withdrawal (19,35) and a hyperdopaminergic state that characterizes protracted abstinence (Fig. 2).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Together with a meta-analysis of rodent studies, our data provide convergent evidence that a hyperdopaminergic state occurs during protracted abstinence. According to the literature and the time-course studies we present here, we propose that dynamical changes take place in the mesolimbic DA system during withdrawal and protracted abstinence, resulting in a hypodopaminergic state that characterizes acute withdrawal (19,35) and a hyperdopaminergic state that characterizes protracted abstinence (Fig. 2).…”
Section: Discussionsupporting
confidence: 56%
“…Experimental support for this view comes from animal work (35) and human PET studies that found reduced availability of striatal D2-like receptors compared with controls (10)(11)(12)(13)(14)(15)(16). Because these PET studies do not provide a coherent picture (20)(21)(22), we used saturated receptor autoradiography techniques to measure the number of DA receptor and DAT-binding sites in postmortem brain tissues of alcoholics and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of this form of LTD was shown after repeated noncontingent cocaine injections (Thomas et al, 2001), cocaine self-administration Moussawi et al, 2009;Kasanetz et al, 2010), ethanol consumption (Jeanes et al, 2011(Jeanes et al, , 2014Spiga et al, 2014), and heroin self-administration . Interestingly, the reduction in LTD is long-lasting in the NAcore and is also observed after 21 days of abstinence from cocaine 838 self-administration .…”
Section: A Long-term Synaptic Plasticitymentioning
confidence: 98%
“…For example, withdrawal from nicotine self-administration shows a similar potentiation (Gipson et al, 2013b), whereas the results are mixed for studies examining the NAc after withdrawal from heroin exposure Shen et al, 2011;Wu et al, 2012). Chronic ethanol induces an increase in mEPSC frequency with no change in amplitude; however, mEPSC frequency is decreased and mEPSC amplitude is increased after withdrawal, indicating that two opposing mechanisms are activated (Spiga et al, 2014). Regardless of the specific change and the specific model used, these data support the perspective that the enduring symptoms of drug addiction may be encoded by synaptic changes in the NAc.…”
Section: A Long-term Synaptic Plasticitymentioning
confidence: 99%
“…For example, withdrawal from long-term ethanol exposure decreases spine density in the amydgala, concomitant with increased anxiety and decreased BDNF-Arc signaling (Pandey et al, 2008). In the NAc, both chronic alcohol drinking and alcohol withdrawal decreased spine density, accompanied by reduction in NMDAR-mediated synaptic Drug-Induced Neuroplasticity currents and hampered LTD Spiga et al, 2014). On the other hand, prolonged intermittent alcohol drinking in cynomolgus monkeys increased the density of dendritic spines and glutamatergic transmission in the putamen, but not in the caudate nucleus (Cuzon Carlson et al, 2011).…”
Section: Ethanol Administered In Vitro Enhanced Ipsps Andmentioning
confidence: 99%